Microbiome profiling and Actinomycetes isolation from tropical marine sponges - Trinset Weeraphan; Chollabuppha Chou; Naphatson Chanthathamrongsiri; Thanchanok Sirirak; Sumaitt Putchakarn; Supakarn Chamni; Wongsakorn Phongsopitanun (AIMS Microbiology)
Marine sponges are well-known for their production of bioactive compounds, many of which are synthesized by their associated symbiotic microorganisms. Among these, Actinomycetes are of particular interest due to their ability to produce secondary metabolites with antimicrobial and antitumor activities. We aimed to investigate the bacterial microbiome of tropical marine sponges, with an emphasis on the diversity and distribution of Actinomycetes, employing both culture-dependent and culture-independent approaches. Five sponge samples (PF01–PF05) were collected from Sichang Island, Chonburi Province, Thailand. The bacterial communities were analyzed using 16S rRNA gene sequencing and bioinformatics tools, revealing a significant microbial diversity dominated by Cyanobacteria, Actinomycetota, and Chloroflexi. Notably, PF01 (Penares nux) exhibited the highest microbial diversity, while PF05 (Cacospongia sp.) had the lowest. Actinomycetes, particularly the genus Micromonospora, were successfully isolated from all samples, with PF03 (Ircinia mutans) yielding the highest number of strains. Culture-independent analysis identified a greater proportion of unculturable Actinomycetes compared to those isolated through traditional methods, underscoring the limitations of culture-dependent techniques. This study enhances our understanding of sponge-associated microbial diversity and highlights the potential for isolating Actinomycetes from these sponges for novel drug discovery and other bioprospective applications.